Pulmonary Tuberculosis Management in Primary Care: The Added Value of a Holistic Assessment Approach - Mardheni Wulandari; Sarah Prima Ayu; Muhammad Aschabul Firdaus; M. Adib Adzikro; M. Agung Dwi Sagaf; M. Aldrich Harsono; Muhammad Fariel (Biomedical Research and Theory Letters, 2026)
Pulmonary tuberculosis (TB) remains a major global public health problem, particularly in developing countries with high population density, limited socioeconomic resources, and constrained healthcare access. Indonesia continues to rank among the countries with the highest TB burden worldwide, emphasizing the need for effective early detection and comprehensive patient-centered management at the primary healthcare level. Although pharmacological treatment through the Directly Observed Treatment Short-course (DOTS) strategy has significantly improved TB control, treatment success is often influenced by psychosocial, behavioral, economic, and environmental determinants that are insufficiently addressed in conventional clinical management. This case report aims to describe the implementation and clinical value of a holistic biopsychosocial assessment approach in the management of pulmonary TB at a primary healthcare facility. A 34-year-old male presented to the Simpur Community Health Center, Bandar Lampung, Indonesia, with a productive cough lasting more than four weeks, weight loss, night sweats, intermittent fever, and decreased appetite. Clinical examination, sputum acid-fast bacilli (AFB) testing, rapid molecular testing, and chest radiography confirmed a diagnosis of drug-sensitive active pulmonary TB. A comprehensive holistic assessment revealed multiple interrelated determinants influencing disease progression and treatment adherence, including malnutrition, psychological anxiety, fear of social stigma, unstable income, smoking habits, overcrowded living conditions, and inadequate household ventilation. The patient underwent integrated management consisting of standard anti-tuberculosis drug therapy, family-based medication supervision, nutritional intervention, psychosocial counseling, infection prevention education, smoking cessation counseling, and environmental modification strategies aimed at improving household ventilation and reducing transmission risk. Follow-up evaluation demonstrated substantial clinical improvement characterized by reduced respiratory symptoms, weight gain, improved treatment adherence, enhanced psychological well-being, and stronger family support. This case highlights the importance of integrating biological, psychological, social, economic, behavioral, and environmental assessments into pulmonary TB management at the primary care level. A holistic approach not only supports successful pharmacological treatment but also improves patient adherence, quality of life, and community-based TB prevention efforts. The findings emphasize that comprehensive patient-centered care should become an essential component of TB management strategies in high-burden settings.